2020
DOI: 10.2147/orr.s239355
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy of a Single Intra-Articular HYMOVIS ONE Injection for Managing Symptomatic Hip Osteoarthritis: A 12-Month Follow-Up Retrospective Analysis of the ANTIAGE Register Data</p>

Abstract: Purpose: The use of ultrasound (US) guidance has allowed hip osteoarthritis to be treated with intra-articular (IA) injections. HYMOVIS ONE (HYADD4-G) is a new hyaluronic acid (HA) derivative product with unusual characteristics, and it has been used with good results in knee osteoarthritis (OA). This study assessed the efficacy and safety of a single HYMOVIS ONE injection in patients affected by symptomatic hip OA. Patients and Methods: This post-marketing cohort study assessed data from the ANTIAGE Register.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Clementi et al 33 observed that in cases of moderate OA, the improvement in pain and function was the same when using one vial of HA with high molecular weight and two vials of HA with medium molecular weight. For Migliore et al, 1 it is safer to use VS with indication of a single intra-articular injection than those with indication of more than one to obtain the same beneficial effects, as it reduces risks and facilitates patient's adherence to treatment. The discussion among experts addressed the fact that the use of VS as a chondroprotective drug in the case of mild hip OA is on the borderline between clinical conviction and literature data, considering that there are no studies demonstrating such an effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clementi et al 33 observed that in cases of moderate OA, the improvement in pain and function was the same when using one vial of HA with high molecular weight and two vials of HA with medium molecular weight. For Migliore et al, 1 it is safer to use VS with indication of a single intra-articular injection than those with indication of more than one to obtain the same beneficial effects, as it reduces risks and facilitates patient's adherence to treatment. The discussion among experts addressed the fact that the use of VS as a chondroprotective drug in the case of mild hip OA is on the borderline between clinical conviction and literature data, considering that there are no studies demonstrating such an effect.…”
Section: Resultsmentioning
confidence: 99%
“…When searching in the literature, the need to associate a subsidiary method to guide hip infiltration is unanimous, due to the risk of injury to the neurovascular bundle and technical difficulty in reaching the joint, in which ultrasound is predominant, both for the simplicity of use and for the absence of risks both for physicians and patients. 1,2,18,20,30,33,34 Statement 9: VS generates cost reduction for the Supplementary Health System, being a cost-effective procedure. Agreement: Strongly in favor Mean: 8.5 Median: 10 Achieved values: 2-10 For specialists, this is a difficult topic, given the scarcity of studies on the subject, especially with regard to national literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Milgore et al conducted a multicenter, retrospective analysis of single HA injection involving 198 patients with hip OA (90.9% KL grade II or III) and demonstrated significantly improved pain and function scores according to VAS (5.3 ± 1.9 vs 6.4 ± 2.2; p = 0.004) and Lequesne Index (7.6 ± 2.4 vs 11.5 ± 4.6; p = 0.008) as well as lower NSAID consumption at 6 months (12.8 ± 3.2 days/month, p = 0.007) and 12 months (9.5 ± 2.1 days/month, p = 0.009) post injection compared to baseline. [48] A case series from Pogliacomi et al investigated the effectiveness of a single intraarticular injection of high molecular weight HA to treat hip OA (Kellgren-Lawrence [KL] grades 1-3). [49•] The authors used HHS and WOMAC outcome scores to evaluate patient response.…”
Section: Hyaluronic Acid (Ha)mentioning
confidence: 99%
“…8) For hip OA, several studies have reported that pain is reduced in the short-term by IA-HA, and function disability is improved. [10][11][12][13][14][15][16] These reports are from Europe and the United States, because the use of HA for hip OA is not covered by insurance in Japan and is therefore rarely used. Hylan G-F 20 is a cross-linked sodium hyaluronate with a high average molecular weight of 6 million Dalton.…”
Section: Introductionmentioning
confidence: 99%